A Barthesian Semiotic Analysis of Domination and Opression Myths in Osama Hajjaj’s Israel-Palestine Caricatures on Instagram - Nadhiyah, Aini Rohtul; Chotimah , Dien Nur (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Political cartoons play a significant role in shaping public meaning because they can convery social criticism and ideology through brief yet powerful visual symbols. As a form of visual discourse, cartoons challenge dominant media narratives and open spaces for interpretation of political events. This study examines how Osama Hajjaj’s cartoons represent the Israel-Palestine conflict, focusing on the myth of Israel domination and oppression. Altough this conflict receives extensive coverage in international media, there remains a gap in understanding the contribution of visual media particularly political cartoons in shaping public perception and ideology. This research employs Roland Barthes’ semiotic theory to analyze Osama Hajjaj’s cartoons on the Israel-Palestine conflict, uploaded on Instagram between July 2024 and February 2025, with reports from The Guardian used a contextual data to interpret visual responses to ongoing discourse. The purpose of this study is to analyze Hajjaj’s cartoons using Barthes’ semiotics to uncover layers of denotative, connotative, and mythological meaning. The findings indicate consistent visual patterns at the denotative, connotative, and myth levels, revealing how the cartoons to empirical media coverage. In doing so, the cartoons are understood not only as symbolic representations but also as critical responses to international media narratives. The study concludes that Hajjaj’s cartoons fuction as a form of visual resistance to media hegemony and hold educational potential in enhancing visual media literacy and critical awareness of the ideologies embedded in digital political representation.